Efektifitas Layanan Bimbingan Kelompok Teknik FGD Untuk Mengurangi Prokrastinasi Akademik Siswa di SMP N 1 Madukara - Maurizka Dwi Apriliani; Erni Hestiningrum; Ulfa Danni Rosada; Hardi Santosa (JURNAL KONSELING GUSJIGANG, 2023)
This study aims to see the effectiveness of Group Guidance Services using thetechnique Focus Group Discussion in minimizing academic procrastination in Class VII F students of SMPN 1 Madukara. The characteristic or distinguishing feature of this research is the use of Group Guidance Services FGD techniques. Where FGD is a focus group discussion, not a free discussion. FGD is a group discussion technique to discuss the same problem, in an informal and relaxed atmosphere. The results of the calculation of the t coefficient using the SPSS program show that tcount= 19,848 compared to ttable with a significance of 5% for dk n-1=8-1=7 is 2.365. This shows that tcount  is greater than ttable, namely 19,848 2,365. So it was concluded that there was a significant difference between the level of student academic procrastination before and after being given FGD services. Artikelinidapatdiaksessecaraterbukadibawahlisensi CC-BY